Teknik Public Speaking Untuk Mengatasi Kecemasan: Studi Kasus Pada Siswa SMP Di Blitar: Studi kasus di SMP Blitar - Karisdayanti, Putri; Nurmalita, Ira; Wulansari, Rizka; Mara Dinanti, Rizki; Puspita Sari, Hesty (Jurnal Pendidikan : Riset dan Konseptual, 2026)
Public speaking anxiety is a common barrier experienced by students, including those at the junior high school level. This study explores practical techniques to help students overcome anxiety in public speaking. Using a qualitative approach with a case study method, data were collected through in-depth interviews with six 9th-grade students in Blitar Regency who had participated in various public speaking competitions. The findings revealed that the main challenges faced by students included fear of making mistakes, limited vocabulary, and low self-confidence. Students employed several strategies to cope with these issues, such as mental preparation, breathing exercises, consuming candy, and selecting comfortable attire. These techniques boosted students’ confidence and reduced their anxiety during public speaking activities. The study offers practical insights for educators in supporting students’ public speaking development through simple yet effective strategies. Keyword: public speaking, anxiety, junior high school students, coping strategies